Iron plaque formed under aerobic conditions efficiently immobilizes arsenic in Lupinus albus L roots. (September 2016) - Fresno, Teresa; Peñalosa, Jesús M.; Santner, Jakob; Puschenreiter, Markus; Prohaska, Thomas; Moreno-Jiménez, Eduardo
Abstract: Arsenic is a non-threshold carcinogenic metalloid. Thus, human exposure should be minimised, e.g. by chemically stabilizing As in soil. Since iron is a potential As immobiliser, it was investigated whether root iron plaque, formed under aerobic conditions, affects As uptake, metabolism and distribution in Lupinus albus plants. White lupin plants were cultivated in a continuously aerated hydroponic culture containing Fe/EDDHA or FeSO4 and exposed to arsenate (5 or 20 μM). Only FeSO4 induced surficial iron plaque in roots. LA-ICP-MS analysis accomplished on root sections corroborated the association of As to this surficial Fe. Additionally, As(V) was the predominant species in FeSO4 -treated roots, suggesting less efficient As uptake in the presence of iron plaque. Fe/EDDHA-exposed roots neither showed such surficial FeAs co-localisation nor As(V) accumulation; in contrast As(III) was the predominant species in root tissue. Furthermore, FeSO4 -treated plants showed reduced shoot-to-root As ratios, which were >10-fold lower compared to Fe/EDDHA treatment. Our results highlight the role of an iron plaque formed in roots of white lupin under aerobic conditions on As immobilisation. These findings, to our knowledge, have not been addressed before for this plant and have potential implications on soil remediation (phytostabilisation) and food security (minimising As in crops). Graphical abstract: Highlights: FeSO4 in hydroponics induced iron plaque formation on the surface of lupin roots. Iron plaque retained As (V) in root surface, mitigating As plant uptake. This iron plaque reduced As transfer to plant shoots. Similar effect may occur in the rhizosphere of oxic soils. Abstract : Iron plaque formation was induced on roots of white lupin under aerobic conditions, thereby mitigating As uptake and its transfer to shoots.